Nuclear Translocation of SGPP-1 and Decrease of SGPL-1 Activity Contribute to Sphingolipid Rheostat Regulation of Inflammatory Dendritic Cells - Anja Schwiebs; Dominique Thomas; Burkhard Kleuser; Josef M. Pfeilschifter; Heinfried H. Radeke (Mediators of Inflammation)
A balanced sphingolipid rheostat is indispensable for dendritic cell function and survival and thus initiation of an immune response. Sphingolipid levels are dynamically maintained by the action of sphingolipid enzymes of which sphingosine kinases, S1P phosphatases (SGPP-1/2) and S1P lyase (SGPL-1), are pivotal in the balance of S1P and sphingosine levels. In this study, we present that SGPP-1 and SGPL-1 are regulated in inflammatory dendritic cells and contribute to S1P fate. TLR-dependent activation caused SGPL-1 protein downregulation with subsequent decrease of enzymatic activity by two-thirds. In parallel, confocal fluorescence microscopy revealed that endogenous SGPP-1 was expressed in nuclei of naive dendritic cells and was translocated into the cytoplasmatic compartment upon inflammatory stimulation resulting in dephosphorylation of S1P. Mass spectrometric determination showed that a part of the resulting sphingosine was released from the cell, increasing extracellular levels. Another route of diminishing intracellular S1P was possibly taken by its export via ATP-binding cassette transporter C1 which was upregulated in array analysis, while the S1P transporter, spinster homolog 2, was not relevant in dendritic cells. These investigations newly describe the sequential expression and localization of the endogenous S1P regulators SGPP-1 and SGPL-1 and highlight their contribution to the sphingolipid rheostat in inflammation.